Characterization of Two Heterogeneous Lethal Mouse-Adapted SARS-CoV-2 Variants Recapitulating Representative Aspects of Human COVID-19 - Yan, Feihu; Li, Entao; Wang, Tiecheng; Li, Yuanguo; Liu, Jun; Wang, Weiqi; Qin, Tian; Su, Rina; Pei, Hongyan; Wang, Shen; Feng, Na; Zhao, Yongkun; et al. (Frontiers in Immunology, 2022)
New emerging SARS-CoV-2 has caused a worldwide pandemic. Several animal models of COVID-19 have been developed and applied to antiviral researches. In this study, two lethal mouse-adapted SARS-CoV-2 variants (BMA8 and C57MA14) with different virulence were generated from different hosts, which are characterized with high viral replication titers in the upper and lower respiratory tract, pulmonary pathology, cytokines storm, cellular tropism, lymphopenia and neutrophilia. Two variants exhibit host genetics-related and age-dependent morbidity and mortality in mice, exquisitely reflecting the clinical manifestation of asymptomatic, moderate and severe COVID-19 patients. Notably, both variants equally weaken the neutralization capacity of the serum derived from COVID-19 convalescent, but the C57MA14 variant showed a much higher virulence than the BMA8 variant in vitro. Q489H substitution in RBD of BMA8 and C57MA14 variants results in the receptors of SARS-CoV-2 switching from hACE2 to mACE2. Additionally, A22D and A36V mutation in E protein were first reported in our study, which potentially contributed to the virulence difference between the two variants. Of note, the protective efficacy of the novel BLP vaccine candidate was validated using the BMA8 or C57MA14-infected aged mice model. The BMA8 and C57MA14 variants-infected models provide a relatively inexpensive and accessible evaluation platform for assessing the efficacy of vaccines and novel therapeutic approaches. This will promote further research in the transmissibility and pathogenicity mechanisms of SARS-CoV-2.